(untitled) (Bulletin of Innovative Research, 2026)
The article examines taboo speech acts as a specific pragmatic phenomenon reflecting cultural, social, and value-based norms of different linguacultures. Particular attention is paid to the analysis of speech acts of prohibition, insult, curse, intimate reference, and silence, which demonstrate varying degrees of acceptability and illocutionary force across cultures. Based on a comparative analysis of several languages and cultures, the study identifies similarities and differences in the realization of taboo speech acts, as well as mechanisms of mitigation, euphemization, and substitution. It is shown that the violation of taboo does not always lead to communicative failure and, in certain contexts, functions as a strategic tool for expressing emotions, power, or group identity. The findings contribute to the development of speech act theory, intercultural pragmatics, and linguacultural studies.